Implementasi Manajemen Bandwidth Dengan Disiplin Antrian Hierarchical Token Bucket (HTB) Pada Sistem Operasi Linux - Nugraha, Muhammad; Utama, Soffin Nahwa (Department of Informatics Engineering, 2016)
Important Problem on Internet networking is exhausted resource and bandwidth by some user while other user did not get service properly. To overcome that problem we need to implement traffic control and bandwidth management system in router. In this research author want to implement Hierarchical Token Bucket algorithm as queue discipline (qdisc) to get bandwidth management accurately in order the user can get bandwidth properly. The result of this research is form the management bandwidth cheaply and efficiently by using Hierarchical Token Bucket qdisc on Linux operating system were able to manage the user as we want.